Treatment of toxoplasmic encephalitis in mice with recombinant gamma interferon. - Suzuki, Y (1990)
The effect of exogenous gamma interferon (IFN-gamma) on toxoplasmic encephalitis in a murine model was evaluated. The brains of CBA/Ca mice chronically infected with the ME49 strain of Toxoplasma gondii have a remarkable inflammatory cell infiltrate. Intravenous administration of six doses (5 x 10(5) U each) of recombinant IFN-gamma (rIFN-gamma) resulted in a remarkable decrease in numbers and foci of inflammatory cells in murine brain parenchyma and perivascular areas 1 day after the last injection of IFN-gamma. Immunoperoxidase staining revealed the presence of tachyzoites only on areas of acute focal inflammation, suggesting that the focal inflammation was caused by the proliferation of tachyzoites. The remarkable reduction in number of foci of acute focal inflammation in the brains of the IFN-gamma-treated mice indicates that the treatment resulted in diminished numbers of tachyzoites in the brains of the infected mice. The effect of rIFN-gamma was dose dependent; injection of 5 x 10(5) U every other day for a total of six doses was effective; injection of either 5 x 10(4), 5 x 10(3), or 5 x 10(2) U was not. This therapeutic effect of rIFN-gamma on encephalitis was not present 2 weeks after the last injection of rIFN-gamma. At that time, mice again had severe inflammation in their brains. Toxoplasma antibody production was not affected by treatment with rIFN-gamma. These results offer support for the value of injection of IFN-gamma in the treatment of toxoplasmic encephalitis in immunosuppressed patients, although its effect appears to be transient.